GERIATRIC NURSING CARE MANAGEMENT WITH A SERVICE EXCELLENCE APPROACH FOR MRS. N WITH HYPERTENSION AT THE ELDERLY SOCIAL SERVICE UNIT (UPTD) BINJAI, NORTH SUMATRA, 2025 - Butar-Butar, Elisabet; Fatiyah; Eva Oktavia; Bagenni Simaremare; Rani Rifka Enjelika Manurung; Djanius Mariati; Aprisilia Tarigan, (Mitra Husada Health Internasional Conference (MIHHICo), 2025)
The elderly stage of life is characterized by a natural decline in physiological function and an increased susceptibility to degenerative diseases such as hypertension. This condition is often referred to as a “silent killer” because it may not present obvious symptoms, yet it can lead to life-threatening complications if left untreated. The purpose of this study was to implement a geriatric nursing care management model using a service excellence approach for Mrs. N, an elderly patient diagnosed with hypertension at the Binjai Elderly Social Service Unit (UPTD) in North Sumatra. A descriptive case study method was applied, integrating a comprehensive nursing process consisting of assessment, nursing diagnosis, care planning, implementation, evaluation, and documentation. Data were collected through interviews, physical assessments, and direct observation. The nursing diagnoses identified during the assessment process included acute pain, sleep pattern disturbance, and knowledge deficit. To address these issues, nursing interventions focused on providing health education, teaching relaxation techniques, and offering emotional and spiritual support tailored to the patient’s needs. These interventions aimed not only to alleviate physical discomfort but also to empower the patient with knowledge and promote holistic well-being through compassionate and patient-centered care. The evaluation revealed significant improvements, including a reduction in pain intensity, better sleep quality, and enhanced understanding of the patient’s health condition. These outcomes indicate that the application of service excellence in geriatric nursing care can positively influence the quality of life of elderly individuals with hypertension. The findings from this study may serve as a valuable reference for future nursing practices, encouraging a more humane, empathetic, and professional approach in delivering healthcare services to older adults.